The Use of Personal Protective Equipment and The Risk of Facial Pressure Sores among Nurses in Covid Isolation Rooms - Sitti Syabariyah; Winy Anggraeni; Anggriyana Tri Widianti; Cyril B. Romero (The Indonesian Institute of Science and Technology Research, 2022)
This study aimed to determine the relationship between the use of personal protective equipment and the risk of facial pressure injury among nurses in the Raudhah 5 room of Muhammadiyah Hospital Bandung (RSMB). This study is a quantitative correlation study with a cross-sectional research design. The research population is 15 COVID-19 isolation nurses in RSMB with a total sampling technique. Bivariate analysis used is the contingency coefficient correlation test. Nurses that used personal protective equipment or more than 50% had a moderate risk of pressure injury as experienced by ten nurses (66.7%). The correlation coefficient test of personal protective equipment obtained a p-value= 0.537. There is no relationship between the use of personal protective equipment to the risk of facial pressure injury on nurses in RSMB. Nurses who use level 3 of PPE, especially in the facial area, should use dressings to prevent the risk of facial pressure injury.